SARI CenTeLLA ASIATICA ASLI BALI MENINGKATKAN SEKRESI TuMouR neCRoSIS FACToR ALPHA (TNF-a) PADA MENCIT YANG DIINFEKSIKAN SALMoneLLA TYPHI - I Nyoman Wande; Sianny Herawati; Ida Ayu Alit Widhiartini; I Wayan Putu Sutirta Yasa; Tjokorda Gede Oka; Ni Made Linawati (Indonesian Association of Clinical Pathologist and Medical laboratory, 2014)
Tumour necrosis factor alpha (TNF-α) is a cytokine produced by macrophages and other mononuclear cells, is a good antibacterial agent against Salmonella spp, especially Salmonella typhi. Centella asiatica is an alternative drug that is expected as an immunostimulant in patients with typhoid fever. Comparing the effectiveness of Centella asiatica extract the original Bali as an immunostimulant and without stimulants in mice infected Salmonella typhi in terms of TNF-α secretion. This study is an experimental study with a post test only with control group design. A total of 20 mice were divided into 4 groups. The first and second groups each given Centella asiatica extract 75 mg/20 g bw (0.5 cc) and without a given extract for 4 weeks. Both groups were inoculated orally Salmonella typhi 106 per mL of bacteria in the second week. The third and fourth groups were given thiamphenicol with Centella asiatica extract 75 mg/20 g bw (0.5 cc) and thiamphenicol without any extract for 4 weeks respectively. Both groups were inoculated orally Salmonella typhi 106 per mL of bacteria in the first day. All groups terminated on fourth week and examination levels of TNF-α by ELISA and gall culture. The mean levels of TNF-α in groups (1–4) is 86.10±2.67 pg/mL, 32.81±11.33 pg/mL, 35.87±3.90 pg/mL and 19.21±2.19 pg/mL respectively. Based on the examination of the gall cultures this study showed positive results in the first and second groups, while a negative result on the third and fourth groups. Based on the One way ANOVA analysis on levels of TNF-α, there are significant differences between the first group with the second group (p<0.05), and between the third and fourth groups also found significant differences (p<0.05) increased levels of TNF-α in mice with Salmonella typhi infection given Centella asiatica extract.